Мышкин и Лебедев. О юродивых и шутах в «Идиоте»(Myškin and Lebedev. On “Good’s Fools” and Buffoons in “Тhe Idiot”) - Egeberg, Erik (Poljarnyj vestnik, 2004)
In this paper the hero of Dostoevskij’s novel "The Idiot", Prince Myškin, is compared to a more humble character of that book, Luk’jan Lebedev, with special regard to their religious teaching and the Russian notions of "jurodivyj" ("God’s fool") and "šut" ("buffoon"). The paper concludes with the assertion that the Prince concentrates on the bright aspects of religion, while Mr. Lebedev, when provoked, emphasizes its more sinister side.